Adding sweet sorghum juice into current dry-grind ethanol process for improving ethanol yields and water efficiency - Appiah-Nkansah, Nana B; Saul, Kaelin; Rooney, William L; Wang, Donghai (International Journal of Agricultural and Biological Engineering, 2015)
Sweet sorghum is a promising energy crop due to its low fertilizer and water requirements, short growth period, and high biomass yield. However, the challenge for sweet sorghum as a feedstock for ethanol production is its short harvest period and the extreme instability of its juice, both of which make achieving a year-round production process difficult. One way to solve this challenge and to meet the growing demand of bio-renewable ethanol is to incorporate sweet sorghum juice into the current dry-grind ethanol process. In the dry-grind process, the whole grain kernel is milled and fermented to produce ethanol. In this study, sweet sorghum juice with varying grain sorghum flour contents was liquefied, saccharified, fermented, and distilled to produce ethanol. Ethanol yield from sweet sorghum juice with the optimum grain sorghum flour loading was about 28% higher than that from the conventional ethanol process. Enzymatic hydrolysis with this process could be reduced by 30 min. The fermentation performance of sweet sorghum juice with grain flour using a raw starch hydrolyzing enzyme was also investigated, and ethanol yield was about 21% higher than that from the conventional process. This innovative technology enabling ethanol production from sweet sorghum juice could improve ethanol yield, save energy, and significantly decrease water use in the current dry-grind ethanol process.Keywords: sweet sorghum, biomass, ethanol yield, hydrolyzing time, conversion efficiencyDOI: 10.3965/j.ijabe.20150802.1513